2022
DOI: 10.3389/fpsyg.2022.996577
|View full text |Cite
|
Sign up to set email alerts
|

Social media and academic success: Impacts of using telegram on foreign language motivation, foreign language anxiety, and attitude toward learning among EFL learners

Abstract: Concerning the ubiquity of social media, this research tried to examine the impacts of using Telegram on Iranian EFL learners’ foreign language motivation, foreign language anxiety, and attitude toward learning. To achieve these purposes, 60 Iranian EFL learners at the intermediate level were selected and randomly divided into two groups: experimental and control. After that, both groups were pretested on motivation and anxiety variables. After pretesting, the participants in the experimental class received tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
3
7
0
Order By: Relevance
“…The Telegram app can lessen the pressure that comes with being evaluated. This result is in line with the results of Zhao et al ( 2022 ), who concluded that the Telegram program may help students better regulate their anxiety while attending language classes.…”
Section: Discussionsupporting
confidence: 92%
“…The Telegram app can lessen the pressure that comes with being evaluated. This result is in line with the results of Zhao et al ( 2022 ), who concluded that the Telegram program may help students better regulate their anxiety while attending language classes.…”
Section: Discussionsupporting
confidence: 92%
“…According to Ref. [ 32 ], who came to the conclusion that the Telegram application might assist students better control their anxiety while taking language lessons, this result is consistent with their findings.…”
Section: Discussionsupporting
confidence: 79%
“…Vygotsky's theory applies to this research context by suggesting that L2 English acquisition necessitates closer attention to diversity with cultures as shaping how female EFL learners feel motivated and engaged. Accordingly, language learning takes place cooperatively in social contexts when instructors deliver content not guided by rote memorization (Zhao et al, 2022). Prevailing cultural opinions and attitudes toward L2 acquisition significantly influence how EFL learners assess their readiness to improve their English proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%